Atypical sensory processing features in children with autism, and their relationships with maladaptive behaviors and caregiver strain. Issue 6 (17th March 2022) - Griffin, Zoe A. M.; Boulton, Kelsie A.; Thapa, Rinku; DeMayo, Marilena M.; Ambarchi, Zahava; Thomas, Emma; Pokorski, Izabella; Hickie, Ian B.; Guastella, Adam J.
Abstract: Atypical sensory processing occurs in up to 97% of children on the autism spectrum. Children who are on the autism spectrum also commonly demonstrate challenging behaviors, and their caregivers report increased levels of strain in daily life. The aim of this study was to explore four sensory processing features; seeking, avoiding, sensitivity, and registration, and their relationships with maladaptive behaviors in children with autism, as well as with caregiver strain. Participants comprised 75 children with autism aged 7–12 years ( M  = 7.81). Caregivers completed three questionnaire measures examining child sensory processing, maladaptive behaviors, and perceptions of caregiver strain. We found avoiding significantly associated with irritability. Avoiding also displayed the strongest relationship with global caregiver strain. Avoiding and seeking were strongly related to hyperactivity/noncompliance (components of maladaptive behavior). A multiple regression was performed to explore how atypical sensory processing features and maladaptive behaviors together predicted caregiver strain. Together, maladaptive behaviors and sensory features accounted for 58% of the variance in total caregiver strain. The only significant individual predictor of total caregiver strain was sensory avoiding, which uniquely accounted for 5.76% of the variation. The findings suggest that atypical sensory processing is associated with overall caregiver strain, above that explained by maladaptive behaviors. Implications for targeted support for the benefit of the child, parents and family unit are discussed. Lay summary: Children who are on the autism spectrum often have differences in sensory processing. These children also tend to show challenging behaviors, and their caregivers can experience increased stress. This study looked at how sensory processing difficulties relate to such behaviors and caregiver stress. We found that both sensory processing and challenging behaviors were related to the amount of stress caregivers felt. This suggests that interventions may benefit from looking at sensory processing features when considering how to help reduce challenging behaviors and caregiver stress.